Critical role of type III interferon in controlling SARS-CoV-2 infection in human intestinal epithelial cells - Stanifer, Megan; Kee, Carmon; Cortese, Mirko; Metz Zumarán, Camila; Triana, Sergio; Mukenhirn, Markus; Kräusslich, Hans-Georg; Alexandrov, Theodore; Bartenschlager, Ralf; Boulant, Steeve (Cell reports, 2020)
Severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) is an unprecedented worldwide health problem that requires concerted and global approaches to stop the coronavirus 2019 (COVID-19) pandemic. Although SARS-CoV-2 primarily targets lung epithelium cells, there is growing evidence that the intestinal epithelium is also infected. Here, using both colon-derived cell lines and primary non-transformed colon organoids, we engage in the first comprehensive analysis of the SARS-CoV-2 life cycle in human intestinal epithelial cells (hIECs). Our results demonstrate that hIECs fully support SARS-CoV-2 infection, replication, and production of infectious de novo virus particles. We found that viral infection elicits an extremely robust intrinsic immune response where interferon-mediated responses are efficient at controlling SARS-CoV-2 replication and de novo virus production. Taken together, our data demonstrate that hIECs are a productive site of SARS-CoV-2 replication and suggest that the enteric phase of SARS-CoV-2 may participate in the pathologies observed in COVID-19 patients by contributing to increasing patient viremia and fueling an exacerbated cytokine response.
Gesehen am 14.09.2020